2014
DOI: 10.1055/s-0034-1370923
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Absence of the Anterior Cruciate Ligament in Monozygotic Twins

Abstract: Cases of congenital absence of the cruciate ligaments are seen rarely in the literature. When reported, they are almost exclusively associated with various additional lower extremity deformities. We report the cases of 15-year-old monozygotic twin brothers. Both brothers presented with right knee pain and instability and were found on magnetic resonance imaging (MRI) to have congenital absence of the right anterior cruciate ligament (ACL). Examination of full length leg radiographs and MRI of the knee showed n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 6 publications
(6 reference statements)
0
10
0
Order By: Relevance
“…In regard to the presentation of this pathology, patients with congenital ACL deficiency may not develop symptoms of instability, likely due to either compensatory mechanisms or a more sedentary lifestyle [15] in which this abnormality would not become apparent. Furthermore, there are some reports of grossly hypertrophied and anteriorly positioned meniscofemoral ligament of Humphrey which could play a role in diminishing instability symptoms in the setting of PCL deficiency [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In regard to the presentation of this pathology, patients with congenital ACL deficiency may not develop symptoms of instability, likely due to either compensatory mechanisms or a more sedentary lifestyle [15] in which this abnormality would not become apparent. Furthermore, there are some reports of grossly hypertrophied and anteriorly positioned meniscofemoral ligament of Humphrey which could play a role in diminishing instability symptoms in the setting of PCL deficiency [6].…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with this condition may not have symptomatic instability if they are able to use muscle forces to provide knee stability. The cases reported with symptomatic instability are likely due to an event that may alter the knee homeostasis making the ACL deficiency manifest [15]. Given the rarity of the condition, there is no consensus regarding the optimal therapeutic approach, although most studies conclude that non-surgical options are the appropriate management despite early degenerative joint disease.…”
Section: Introductionmentioning
confidence: 99%
“…Sonn and Caltoum reported a case of 15-year-old monozygotic brothers that were high-level athletes with congenital absence of the right ACL that subsequently both underwent ACL construction with bone-patellar tendon-bone autograft [18]. Astur et al reported a case of twin brothers who were both professional judo athletes that sustained similar ACL tears one year apart but underwent surgery on the same day by the same surgeon that utilized the same technique and graft type (hamstring tendon graft with femoral and tibial interference screws) [6].…”
Section: Discussionmentioning
confidence: 99%
“…Familial presentation of this pathology was rarely described in the English literature [3, 5, 6], even if heritability was suspected. According to Frikha et al [3], congenital cruciate ligament agenesis is autosomal dominantly transmitted with variable prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Sonn and Caltoum [5] reported on 15-year-old male monozygotic twins with symptomatic ACL agenesis. Both underwent ligament reconstruction with a patellar graft.…”
Section: Discussionmentioning
confidence: 99%